"I was made to feel very discriminated against as an anglo-saxon". (5th May 2015) - Mark Vicars; Dr Jon Austin, Dr; Faulkner, Julie; Crowhurst, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Critical discussion of the social conditions that shape educational thinking and practice is now embedded in accredited teacher education programmes. Beneath beliefs that critique of educational inequality is desirable, however, lie more problematic questions around critical pedagogies, ethics and power. Emotional investments can work to protect habituated ways of thinking, despite attempts to move students beyond their comfort zone. This strategic process can shift attitudes and promote intellectual and emotional growth, but can also produce defensive reactions. This paper, a self-study in relation to an incident in a tertiary education programme, examines how student feedback on content and pedagogy positions teachers and learners. The purpose of this paper is to frame and reframe ways in which learner feedback to critical approaches might be read. The argument examines, through dialogue, the potential of disruptive teaching approaches for recontextualising both learner and teacher response. Such exploration articulates particular tensions and challenges inherent in critical teacher education pedagogies. Design/methodology/approach – This is a reflective practitioner piece – involving journaling and the use of dialogue – to explore a critical incident. Findings – This is an exploratory piece – the authors explore the workings of tension in critical/poststructural pedagogical work. Originality/value – The deployment of dialogue as a method and as a way of presenting key issues is somewhat novel. The paper works through quite complex terrain in an accessible and reasonably clear fashion.